Depolicing: When Police Officers Disengage - Oliver, Willard M. (Lynne Rienner Publishers, 2019)
Depolicing--the withdrawal from proactive law enforcement by officers on the line--has become an increasing concern within both police departments and the communities that they serve. Willard Oliver, a former policeman himself, draws on extensive interviews with officers in a variety of jurisdictions to explore how prevalent depolicing has become, why officers engage in it, and what can be done to minimize it. With officer behavior under more and more intense scrutiny, Depolicing is a uniquely important contribution to ongoing debates.